SOSIALISASI DAN PENDAMPINGAN PAKET TEKNOLOGI HAYATI UNTUK BUDIDAYA CABE DI KAWASAN PESISIR BENGKULU - Yudhy Harini Bertham; Abimanyu Dipo Nusantara; Sukisno Sukisno (DHARMA RAFLESIA, 2018)
Pepper plants that grow in coastal areas facing a multiple stress i.e high temperatures, strong winds, drought, salinity, and nutrient deficiencies. Cultivation of plants in coastal areas requires specific technology, but cheap and environmentally friendly.Socialization, training, and mentoring implemented to improve the ability of farmers to implement the cultivation of high yielded chillies in coastal areas. The methods implemented namely (1) socialization potential of coastal land for plant cultivation and the technology needed, (2) training production of biocompost and arbuscular mycorrhizal fungi inoculant, and (3) demoplot pepper cultivation in coastal lands. The activities carried out in the Desa Pekik Nyaring and Beringin Raya, Central Bengkulu Regency, Bengkulu province. Demoplot arranged Split-split plot with a randomized block design Complete two-factor with the location, genotype chili and fertilizer as the main plot, subplot, and sub-sub plot. The results show that farmers can absorb the information and training well to produce biocompost and arbuscular mycorrhizal fungi inculant. Desa Beringin Raya is more potential for pepper cultivation compared Desa Pekik Nyaring. Better technology need to be formulated to pepper cultivation in that village. Keywords: pepper, mycorhiza, organic, coastal area